Analyses of DNA variants in Malays with Hereditary Nonpolyposis Colorectal Cancer (HNPCC) - Zakaria, Andee Dzulkarmaen (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2017)
Hereditary Nonpolyposis Colorectal Cancer (HNPCC) is caused by germline mutations in any of the Mismatch Repair (MMR) genes; MLH1, MSH2, MSH6 and PMS2 including EPCAM gene which is located upstream the MSH2 gene. This study aimed to investigate the underlying genetic variants in Malay HNPCC and of possible genes contributing to the risk of HNPCC. Thirty-two Malay HNPCC patients' samples were analyze by using immunohistochemistry and direct DNA sequencing of MLH1 and MSH2 genes. Seven patients with intact protein expression were selected for further whole genome sequencing. Seven possible mismatch mutations and seven Single Nucleotide Polymorphisms (SNPs) were discovered. By the whole genome sequencing data, a number of insertions and deletions (indels) and SNPs were identified. Nine rare variant from seven genes were also discovered in this study. Of the seven genes, two genes; CDK11B was known play a role in cell cycle progression and MUC6 was associated with the outcome of colorectal cancer. A more comprehensive study and analysis in larger population is required to determine more conclusively pathogenic nature of the genetic variants predicted in silico in the current study